2015
DOI: 10.18632/oncotarget.6418
|View full text |Cite
|
Sign up to set email alerts
|

Metformin suppresses hypoxia-induced stabilization of HIF-1α through reprogramming of oxygen metabolism in hepatocellular carcinoma

Abstract: Overexpression of hypoxia-induced factor 1α (HIF-1α) has been shown to be involved in the development and progression of hepatocellular carcinoma (HCC). HIF-1α should therefore be a promising molecular target for the development of anti-HCC agents. Metformin, an established antidiabetic drug, has proved to also be effective in treating cancer although the precise underlying mechanisms of this activity are not fully elucidated. The aim of this study was to investigate the effects of metformin on the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 38 publications
5
68
0
5
Order By: Relevance
“…Metformin reduced levels of HIF‐1α mRNA and protein in hepatocellular and squamous cancer cells . Metformin reduced HIF‐1α protein levels by suppressing mitochondrial respiration thereby reducing cellular hypoxia . Metformin improved diastolic function in diabetic rats .…”
Section: Oral Hypoglycemic Agents As Potential Therapies For Hfpef Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin reduced levels of HIF‐1α mRNA and protein in hepatocellular and squamous cancer cells . Metformin reduced HIF‐1α protein levels by suppressing mitochondrial respiration thereby reducing cellular hypoxia . Metformin improved diastolic function in diabetic rats .…”
Section: Oral Hypoglycemic Agents As Potential Therapies For Hfpef Acmentioning
confidence: 99%
“…128 Metformin reduced HIF-1α protein levels by suppressing mitochondrial respiration thereby reducing cellular hypoxia. 129 Metformin improved diastolic function in diabetic rats. 130 Analysis of the REACH patient registry demonstrated a 24% reduction in heart failure related mortality in patients taking metformin.…”
Section: Oral Hypoglycemic Agents As Potential Therapies For Hfpef mentioning
confidence: 99%
“…In-vivo studies on hepatocellular carcinoma xenografts have shown that metformin improves cellular oxygenation ability and decreases mitochondrial oxygen consumption, thus suppressing hypoxia-induced HIF-1α accumulation. These effects form the basis of anti-cancer activity of metformin, particularly against hepatocellular carcinoma [18]. …”
Section: Preclinical Datamentioning
confidence: 99%
“…32,33 Thus, the AMPK-mTOR could be affected and lead to cell cycle arrest and apoptosis. 34 In fact, molecular or even therapeutic treatment of HCC by inhibiting HIF-1α, such as HSP90 35 and Metformin, 36 The epithelial-mesenchymal transition (EMT) is a morphogenetic process that results in a loss of epithelial characteristics and acquisition of a mesenchymal phenotype and has become one of the most exciting and increasingly investigated areas in the oncology field. [37][38][39] During the process, ZEB1 and E-box-binding transcription factors are reportedly involved in the tumorigenesis of various malignancies.…”
Section: Discussionmentioning
confidence: 99%